Political Participation of Women in the Chilean Constitutional Process [Participación Política de Las Mujeres en el Proceso Constituyente Chileno] - Figueroa-Rubio, P (Univ Nacional de Educacion a Distancia (UNED), 2022)
This article analyzes the historical and political features of the development of women s political participation and its special importance in the incorporation into the constituent process in Chile, where for the first time in the world there will be a constituent body elected with parity. We will analyze and explain the social contract and the participation of women in decision-making (the development of women s political participation in the constitutional history of Chile); the incorporation of the quota law in 2015 as a precedent for parity; the difficulties that have had to overcome and the legal devices used to obtain a guaranteed quota in the future constituent body, to -finally- point out some central organic and programmatic axes that must be taken into account in the next constituent process to incorporate, thus, the gender perspective in the future constitutional text. © UNED. Revista de Derecho Político